In vitro determination of prebiotic potential of aqueous extract of horse chestnut by-product. (July 2019) - Przyborska, Joanna; Hall, Michael C.; Concannon, Mary
Highlights: Chemical composition of horse chestnut by-product was established. A new formula for determination of Prebiotic Index (PI) was developed. All probiotic strains grown on horse chestnut extract (HCE) gave positive PI score. Lactic and/or acetic acids were produced by probiotic strains grown on HCE.